Prenatal Endotoxin Exposure Induces Fetal and Neonatal Renal Inflammation via Innate and Th1 Immune Activation in Preterm Pigs - Muk, Tik; Jiang, Ping-Ping; Stensballe, Allan; Skovgaard, Kerstin; Sangild, Per Torp; Nguyen, Duc Ninh (Frontiers in Immunology, 2020)
Abstract Chorioamnionitis (CA) predisposes to preterm birth and affects the fetal mucosal surfaces (i.e. gut, lungs, and skin) via intra-amniotic (IA) inflammation, thereby accentuating the proinflammatory status in newborn preterm infants. It is not known if CA may affect more distant organs, such as the kidneys, before and after preterm birth. Using preterm pigs as a model for preterm infants, we investigated the impact of CA on fetal and neonatal renal status and underlying mechanisms. Fetal pigs received an IA dose of lipopolysaccharide (LPS), were delivered preterm by cesarean section three days later (90% gestation), and compared with controls (CON) at birth and at postnatal day five. Plasma proteome and inflammatory targets in kidney tissues were evaluated. IA LPS-exposed pigs showed inflammation of fetal membranes, higher fetal plasma creatinine, and neonatal urinary microalbumin levels, indicating renal dysfunction. At birth, plasma proteomics revealed LPS effects on proteins associated with renal inflammation (up-regulated LRG1, down-regulated ICA, and ACE). Kidney tissues of LPS pigs at birth also showed increased levels of kidney injury markers (LRG1, KIM1, NGLA, HIF1A and CASP3), elevated molecular traits related to innate immune activation (infiltrated MPO+ cells, complement molecules, oxidative stress, TLR2, TLR4, S100A9, LTF, LYZ) and Th1 responses (CD3+ cells, ratios of IFNG/IL4 and TBET/GATA3). Unlike in plasma, innate and adaptive immune responses in kidney tissues of LPS pigs persisted to postnatal day 5. We conclude that prenatal endotoxin exposure induces fetal and postnatal renal inflammation in preterm pigs with both innate and adaptive immune activation, partly explaining the potential increased risks of kidney injury in preterm infants born with chorioamnionitis.